Drivers of business model innovation in micro and small enterprises: evidence from Egypt as an emerging economy - Rasha A. A. ElNaggar; Mayar Farrag ElSayed (Future Business Journal)
Abstract Despite its recognition as a resilience strategy, there is a scarcity of research on business model innovation (BMI) in micro and small enterprises in emerging economies. Business model innovation drivers in micro and small enterprises may differ from those in large firms in developed economies. In micro and small businesses, BMI is determined by the dynamic capabilities of the business, as well as the ability of the business owner to reconfigure and exploit its resources in a way that creates market value. This is one of few studies that connects the concepts of social capital and  market orientation to explain business model innovation and its consequences in a turbulent business environment. This study investigates the impact of managerial ties, business owner market orientation and perceived environmental uncertainty as drivers to BMI. Also, it investigates the effect of BMI on business performance. The results of analyzing the responses of 426 micro and small enterprises by Smart PLS 3.3 show that business model innovation mediates the relationship between business ties and business performance. Surprisingly, the results proved that micro and small business owners adopting reactive market orientation, contribute to BMI more than those adopting proactive market orientation. The findings emphasize the importance of micro and small business owner in driving BMI. This study ensures that BMI is a function of how resources can be deployed and configured dynamically to generate value.